2020
DOI: 10.1007/s40471-020-00244-3
|View full text |Cite
|
Sign up to set email alerts
|

Older Women’s Perspectives Driving Mammography Screening Use and Overuse: a Narrative Review of Mixed-Methods Studies

Abstract: Purpose of Review Examining what older women know and perceive about mammography screening is critical for understanding patterns of under- and overuse, and concordance with screening mammography guidelines in the USA. This narrative review synthesizes qualitative and quantitative evidence around older women’s perspectives toward mammography screening. Recent Findings The majority of 43 identified studies focused on promoting mammography screening in women of different ages, with only four studies focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 86 publications
1
10
1
4
Order By: Relevance
“…Findings from this study support that de-implementation likely works differently than implementation processes and is challenging because it works against prevailing practices and beliefs that reinforce the importance of mammography screening [ 1 , 43 ]. Similar to other studies, older women in our sample hold strong intentions to continue annual mammography screening [ 29 , 44 , 45 ]. Intention has shown to be a strong predictor of mammography screening cessation [ 46 ] and should be examined in light of factors that act as barriers and facilitators of mammography screening [ 47 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Findings from this study support that de-implementation likely works differently than implementation processes and is challenging because it works against prevailing practices and beliefs that reinforce the importance of mammography screening [ 1 , 43 ]. Similar to other studies, older women in our sample hold strong intentions to continue annual mammography screening [ 29 , 44 , 45 ]. Intention has shown to be a strong predictor of mammography screening cessation [ 46 ] and should be examined in light of factors that act as barriers and facilitators of mammography screening [ 47 ].…”
Section: Discussionsupporting
confidence: 85%
“…These findings support the broader notion that racial/ethnic minority populations are also susceptible to overuse that is perpetuated by providers and the operations of the system [ 36 , 56 , 57 ]. To date, few studies on de-implementation capture the perspectives and experiences of ethnically diverse populations or of older women more broadly [ 29 ]. In fact, a recent scoping review of de-implementation science theories, models, and frameworks found only two that account for the role of patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Limited available research suggests that screening mammography among older women may be habitual and perceived as reassuring and easily accessible. 12,15,[19][20][21] However, very little is known about older women's perspectives and experiences with regard to reducing or stopping mammography, particularly among racial or ethnic minority women in the US or samples from racially and ethnically diverse populations. 21 To address this gap, this study seeks to provide an in-depth understanding of the perspectives and preferences of older, ethnically diverse women as they relate to continued screening and potential overuse of routine breast cancer screening.…”
Section: Introductionmentioning
confidence: 99%